2010
DOI: 10.1016/j.neuroscience.2010.04.052
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent effects of κ-opioid receptor stimulation on cocaine-induced stereotyped behaviors and dopamine overflow in the caudate–putamen: an in vivo microdialysis study

Abstract: Abstractκ-Opioid receptor stimulation attenuates psychostimulant-induced increases in extracellular dopamine in the caudate-putamen (CPu) and nucleus accumbens of adult rats, while reducing cocaine-induced locomotor activity and stereotyped behaviors. Because κ-opioid receptor agonists (e.g., U50,488 or U69,593) often affect the behavior of preweanling rats in a paradoxical manner, the purpose of the present study was to determine whether κ-opioid receptor stimulation differentially affects dopaminergic functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
3
6
0
Order By: Relevance
“…Our findings are consistent with previously reported KOR-mediated reduction in BLA excitability in adolescents (Huge, Rammes, Beyer, Zieglgansberger, & Azad, 2009). Ultimately, these neurophysiological effects would produce an anxiolytic effect in adolescents, consistent with previously demonstrated anxiolytic effects of KOR agonists in stress-naïve adolescents (Alexeeva, Nazarova, & Sudakov, 2012;Anderson, Morales, Spear, & Varlinskaya, 2014;Chen et al, 2015;Collins, Zavala, Nazarian, & McDougall, 2000;Cortez et al, 2010;McDougall, Garmsen, Meier, & Crawford, 1997;Nizhnikov, Pautassi, Varlinskaya, Rahmani, & Spear, 2012;Privette & Terrian, 1995).…”
Section: Introductionsupporting
confidence: 85%
“…Our findings are consistent with previously reported KOR-mediated reduction in BLA excitability in adolescents (Huge, Rammes, Beyer, Zieglgansberger, & Azad, 2009). Ultimately, these neurophysiological effects would produce an anxiolytic effect in adolescents, consistent with previously demonstrated anxiolytic effects of KOR agonists in stress-naïve adolescents (Alexeeva, Nazarova, & Sudakov, 2012;Anderson, Morales, Spear, & Varlinskaya, 2014;Chen et al, 2015;Collins, Zavala, Nazarian, & McDougall, 2000;Cortez et al, 2010;McDougall, Garmsen, Meier, & Crawford, 1997;Nizhnikov, Pautassi, Varlinskaya, Rahmani, & Spear, 2012;Privette & Terrian, 1995).…”
Section: Introductionsupporting
confidence: 85%
“…For example, administration of various KOR agonists attenuated psychostimulant-induced locomotor activity in adults but not preweanling rats (McDougall et al 1997; Collins et al 2000). Likewise, U50,488 attenuated cocaine-induced dopamine release in adults but not preweanling rats (Cortez et al 2010). Although at least one study has shown that KOR agonists can also produce conditioned odor aversions in infant rat pups (Barr et al 1994), in other work, an ontogenetic switch has been reported in the effects of KOR agonists, with DYN shown to be a powerful appetitive reinforcer in neonatal rats (Petrov et al 2006), in contrast to the aversive properties of KOR agonists consistently demonstrated in adult rats.…”
Section: Discussionmentioning
confidence: 99%
“…In support, KOR agonists inhibit presynaptic glutamate release and post-synaptic NMDAR potentials [53,7577] and infusion of KOR agonists to the VTA inhibit midbrain dopaminergic cells [78,79]. Moreover, intra-VTA KOR activation influences psychostimulant effects, decreasing sensitization to cocaine seeking [80] and attenuating cocaine-induced repetitive motor behavior [81]. Recently, cocaine-reinstatement was found to be dampened among squirrel monkeys administered a KOR agonist in a nor-BNI-dependent manner [82].…”
Section: Discussionmentioning
confidence: 99%